TESIS ROBERT KUTTNER DAN MENGUATNYA KELOMPOK POPULIS KANAN DI INDONESIA - Bustomi Bustomi (Institut Dirosat Islamiyah Al-Amien Prenduan, 2023)
This paper tries to see why in post-reform Indonesia, right-wing populist groups strengthened using the knife of analysis from Robert Kuttner in his book entitled Can Democracy Survive Global Capitalism. Robert Kuttner mentions 5 factors causing the rise of right-wing populism. First, there is a process of convergence between the development of capitalism and the strengthening of democratic politics. Second, there was a significant political shift. The third is the phenomenon of undemocratic globalization. Fourth, it is the implication of the third factor which greatly influences political spaces. Fifth, there is socio-political vulnerability.